Detection of cytomegalovirus using PCR in serum from renal transplant recipients. Issue 6 (June 1995) - Cunningham, R; Harris, A; Frankton, A; Irving, W
Abstract : AIMS–To develop a polymerase chain reaction (PCR) assay for the detection of cytomegalovirus (CMV) DNA in serum and leucocytes of renal transplant recipients and compare this assay with CMV culture and serodiagnosis. METHODS–Monthly specimens were obtained from 12 patients starting immediately before transplant. CMV infection was monitored by IgM enzyme linked immunosorbent assay, virus culture and PCR on serum and leucocytes. RESULTS–Two of four IgG positive patients had reactivation of CMV disease confirmed by culture, three of eight seronegative patients had a primary infection, one confirmed by serology and two by culture. PCR was positive earlier than conventional methods in three cases and concurrently in two. No positive PCR reactions occurred in the seven patients who remained negative by culture and serology. CONCLUSIONS–CMV DNA is detectable in serum; serum may be positive before virus is detectable by buffy coat culture; and PCR may be useful as an early indication of potential CMV disease in renal transplant recipients.